1992
DOI: 10.1007/bf01962703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of valproate on xenobiotic biotransformation in rat liver

Abstract: Male Wistar rats were in vivo exposed for 2 weeks to 100 micrograms/ml sodium valproate by subcutaneous implantation of osmotic pumps and hepatocytes were isolated. As an in vitro model co-cultures of rat hepatocytes with epithelial cells were daily treated with valproate (25, 50, 100, 200 micrograms/ml) for 2 weeks. In both models the cytochrome P-450 content and the enzymatic activities of 7-ethoxycoumarin O-deethylase, aldrin epoxidase and glutathione S-transferase were determined in valproate-treated hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…VPA reduces plasma GSH level by inhibition of GSH synthesis and glutathione disulfide (GSSG) reduction [48], and the acceleration of GSH degradation. VPA also inhibits GSH peroxidase [47] and GSH-S-transferase [52]. Thus, VPA damages GSH system critically.…”
Section: Suggested Explanation Of the Teratogenicity Of Vpa By The Almentioning
confidence: 98%
“…VPA reduces plasma GSH level by inhibition of GSH synthesis and glutathione disulfide (GSSG) reduction [48], and the acceleration of GSH degradation. VPA also inhibits GSH peroxidase [47] and GSH-S-transferase [52]. Thus, VPA damages GSH system critically.…”
Section: Suggested Explanation Of the Teratogenicity Of Vpa By The Almentioning
confidence: 98%
“…In addition, VPA and TSA are known to be metabolized by cytochrome P450 (CYP) biotransformation enzymes and can increase and/or decrease their activities and/or expression, thereby affecting mechanisms that control drug disposition (Fisher et al ., 1991; Rogiers et al ., 1992, 1995; Isojärvi et al ., 2001; Wen et al ., 2001; Bort et al ., 2004; Cerveny et al ., 2007; Nelson-DeGrave et al ., 2004; Hooven et al ., 2005; Snykers et al ., 2007; Kiang et al ., 2006). Because several CYP enzymes metabolizing a variety of drugs (CYP1A1, 1B1 and 3A4) were found to be expressed in neuroblastoma cells (Poljaková et al ., 2009), here we also investigated whether their expression is influenced by VPA and TSA in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that prolonged exposure of rats to VPA results in the self-inducing metabolism of the agent (Fisher et al, 1991). Moreover, Rogiers et al (1992Rogiers et al ( , 1995 have found VPA to be a potent inducer of genes of the rat Cyp2b subfamily, in particular, Cyp2b1 and Cyp2b2. Recently, Eyel et al (2006) have found out that VPA does not affect expression of rat Cyp3a2, an ortholog of human CYP3A4, whereas valpromide, the primary amide of VPA that reveals no HDAC-inhibitory activity, was shown to induce this gene by a nonspecific mechanism.…”
mentioning
confidence: 99%